Studi Pustaka : Strategi Konservasi Pesisir untuk Mencegah Kehilangan Habitat Terumbu Karang di Perairan Indonesia - Hirliana, Norma; Ariati, Zulhia (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to examine effective coastal conservation strategies in preventing coral reef habitat loss in Indonesian waters. Coral reefs play a very important role in maintaining the balance of marine ecosystems, but they face serious threats, such as climate change, pollution, destructive fishing, and unsustainable exploitation of natural resources. Through this literature review, various conservation approaches that have been implemented in Indonesia, both community-based, government policies, and international initiatives, are analyzed to determine their effectiveness in protecting coral reefs. In addition, this study also explores the challenges faced in implementing conservation strategies and opportunities to strengthen collaboration between the government, communities, and the private sector. The results of this study are expected to provide useful recommendations in the development of more holistic conservation policies and strategies to protect and restore coral reef ecosystems in Indonesia.